Associação “Arte da Terra” : das mãos das mulheres artesãs às relações educativas construídas no processo de autogestão do trabalho - Polini, Ilza Nunes da Cunha (2012)
In the District of Progresso in Tangara da Serra-MT, six artisan women dedicate themselves to clay modeling, for solidarity, in the sharing of the work for the production and creation of cultural products and ornamental objects which represent characteristic aspects of their lifestyle and the local culture. Fountains and jugs of water, birds like the wood ibis and the tanagers, decorative wall plates, pots and other pottery pieces are created by their hands. In the present dissertational text we put forward the research which had been carried out during the Master Course in Education during the period of 2010 and 2011, whose objective was to comprehend the threads which weave the relations between work and education. We have highlighted the relation produced by the artisan women as pedagogical agents and the “learning spaces” in their experience to produce arts with clay. From a “study case” as covered methodological perspective, we have observed the artisan women in their production process, we have taken part in the daily experience of their duties, we have individually interviewed each one of them and we have talked to the municipal solidary economy secretary of Tangara da Serra, as well as, long and meaningful collective conversations, while they had been carrying out their activities, such as: at the artisanal products and foods fair in the town, at the commercialization store of their products and at the the workshop for the creation of their pieces. The annotations had been made in a “Field Diary”, the interviews had been recorded and transcribed in full, after they had been authorized, as well as the photographs, through an “Authorization Term”. The work dimensions as “educational principle” from Gramsci’s concept were crucial to establish the meeting points between the economical and the productive processes. We have discoursed about the “knowledge relations” built by women, where the meaning of collective production is expressed in the guarantee of control of their productions. We have based in Karl Marx to understand the work matters and its conditionings, because we had noticed that the artisan women’s group, through the creation of strategies and conditions, which assure the improvement in their lifestyle and well-being in the world had been attached to the increase in value of the work in a perspective which points to the self-management. It has been important to notice in Tiriba the “pedagogy of the associated production” in the way the six women meet to produce their artwork and their knowledge. Our analysis has been carried out from the study of these authors, of the methodological course developed and the reflections resulted from the historical and dialectical materialism. We have highlighted that by following the artisan women’s group we have been able to notice that they have been living a dispute for legitimation and social validation process in the existence production linked to the enhanced life reproduction. They use the work process and contribute to the construction of their worlds. They point to the understanding that the reality isn’t, it is being and therefore is susceptible to transformation. It is possible to say that the artisan women’s experience come up as an opportunity to claim their rights to understand the social relations built in the “learning spaces” and the role they play there. Therefore it is educational work.